Board role performance in service organisations: the importance of human capital in the context of a developing country - Nkundabanyanga, Stephen K.; Balunywa, Waswa; Tauringana, Venancio; Ntayi, Joseph M. (Social Responsibility Journal., 2014)
The purpose of this paper is to draw from multiple theories of upper echelons, stakeholder, agency, resource-based view and stewardship to establish the extent to which human capital (other than that of the board itself) in service organisations affect board role performance in those service sector firms. Design/methodology/approach – This study is cross-sectional and correlational. Analyses are conducted using SPSS and Analysis of Moment Structures software on a sample of 128 service firms in Uganda. Findings – Findings reveal that dimensions of employee safety, entrepreneurial skills, entrepreneurial development, employee welfare and employee relations fit the model of human capital and predict up to 69.1 per cent of the variance in board role performance. The results of this study reveal that board role performance is affected by prior decisions, for example, to invest in corporate social responsibility (CSR) activities, targeting employees that augment firm characteristics like existence of appropriate human capital. Essentially, an improvement in the quality of human capital explains positive variances in board role performance. Research limitations/implications – Cross-sectional data do not allow for testing of the process aspect of the models; however, they provide evidence that the models can stand empirical tests. Additional research should examine the process aspects of human capital and board role performance. Practical implications – Most companies in developing nations have relied on normative guidelines in prescribing what boards need to enhance performance, probably explaining why some boards have not been successful in their role performance. This research confirms that appropriate human capital, which can be leveraged through CSR ideals of employee safety, recognition, welfare and training in entrepreneurship, consistent with the stakeholder theory, can facilitate the board in the performance of its roles. In the developing country context, organisations’ boards could use these findings as a guideline, that is, what to focus on in the context of human capital development in organisations because doing so improves their own role performance. Originality/value – This study is one of the few that partly account for endogeneity in the study of boards, a methodological concern previously cited in literature (Bascle, 2008; Hamilton and Nickerson, 2003). Empirical associations between board role performance and organisational performance would not be useful unless we are able to grasp the causal mechanisms that lie behind those empirical associations (Hambrick, 2007). Thus, this study contributes to literature that tries to account for variances in board role performance and supports a multi-theoretical approach as a relevant framework in the study of human capital and board role performance.
Keywords: Human capital; Uganda; CSR; Developing country; Board role performance; Service firms